Networked : Towards Urban Resilience and Economic Growth in Vietnam’s Mekong Delta - World Bank (World Bank, Washington, DC, 2021)
This study of seven provincial capitals in Vietnam’s Mekong Delta region, conducted in cooperation with the Vietnam Government, is intended toinform government decision-making on strengthening disaster and climate resilience in these cities, to enable them to contribute to regional economic growth and resilience. The study contributes to the World Bank’s long-term multi-sectoral engagement with the Vietnam Government on the Mekong Delta region, which includes support for a development policy operation currently under preparation and a delta plan.